Analysis of The Impact of Liquidity, Capital Structure, and Asset Growth on The Value of Mining Companies in The Coal Subsector in Indonesia - Ferly S. Rey; Ivonne S. Saerang; Hizkia H. D. Tasik (Journal Research of Social Science, Economics, and Management, 2026)
This study aimed to analyze the impact of liquidity, capital structure, and asset growth on firm value in coal mining subsector companies listed on the Indonesia Stock Exchange (IDX). The phenomenon of global coal price volatility and energy transition policies provided an important backdrop for examining the factors influencing market valuation in this sector. The population consisted of 27 coal mining companies. Using a purposive sampling method, 22 companies were selected as the research sample over the observation period 2021–2024, resulting in 88 panel observations. The data were analyzed using panel data regression, with the Fixed Effects Model (FEM) selected and estimated using the Panel EGLS (cross-section weights) method to address heteroskedasticity issues. The results indicated that, simultaneously, liquidity, capital structure, and asset growth had a significant effect on firm value. Partially, capital structure had a positive and significant effect on firm value, supporting the Trade-Off Theory, which suggests that debt usage provides tax shield benefits for coal mining companies. In contrast, asset growth had a negative and significant effect, indicating that overly aggressive asset expansion without corresponding profitability improvements is negatively perceived by the market. Meanwhile, liquidity was found to have no significant effect on firm value in this sector. The Adjusted R-squared value of 0.7120 indicated that the independent variables explained 71.20% of the variation in firm value.